Morphology made for movement: formation of diverse stomatal guard cells - Spiegelhalder, Roxane; Raissig, Michael Thomas (Current opinion in plant biology, 2021)
Stomata constantly open and close to optimize gas exchange. While the genetic programme guiding early development is well described, the formation of functional guard cells remains enigmatic. This review highlights recent findings on the developmental and morphogenetic processes shaping this essential and morphologically diverse cell type in Arabidopsis and grasses.
Gesehen am 01.12.2021